2005
DOI: 10.1038/sj.npp.1300666
|View full text |Cite
|
Sign up to set email alerts
|

Association of BDNF Serum Concentrations with Central Serotonergic Activity: Evidence from Auditory Signal Processing

Abstract: Disturbances of serotonergic neurotransmission in the brain have been implicated in the pathogenesis and maintenance of several psychiatric disorders. According to recent preclinical and clinical studies, the loudness dependence of auditory evoked potentials (LD) is related to the central serotonergic neurotransmission in humans. As the serotonergic phenotype has been reported to be associated with brain-derived neurotrophic factor (BDNF), we studied whether BDNF serum concentrations are related to LD in 109 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Irrespective of the medication used, better treatment outcome was associated with higher BDNF plasma levels [143]. Moreover, BDNF polymorphism and serum level have been connected with anxiety, risk of depression, neuroticism and serotonergic neurotransmission [145,146,147,148,149]. Augmentation of antidepressants with lithium is currently the best-evidenced augmentation therapy in the treatment of depressed patients who do not respond to antidepressants [150] and also lithium augmentation leads to a BDNF increase [143].…”
Section: Depression As a Neurodegenerative Disordermentioning
confidence: 99%
“…Irrespective of the medication used, better treatment outcome was associated with higher BDNF plasma levels [143]. Moreover, BDNF polymorphism and serum level have been connected with anxiety, risk of depression, neuroticism and serotonergic neurotransmission [145,146,147,148,149]. Augmentation of antidepressants with lithium is currently the best-evidenced augmentation therapy in the treatment of depressed patients who do not respond to antidepressants [150] and also lithium augmentation leads to a BDNF increase [143].…”
Section: Depression As a Neurodegenerative Disordermentioning
confidence: 99%
“…PI3K signaling is triggered by a variety of growth factors including brain-derived neurotrophic factor (BDNF) [2,3], which has been implicated in bipolar disorder, depression, depression-related personality traits and anxiety [2,4,5,6,7]. Decreased expression of BDNF contributes to stress-related mood disorders and the upregulation of BDNF plays a role in the actions of different antidepressant treatments [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the relationship between the LDAEP and serotonergic neurotransmission, while promising, requires more direct validation. Given the lack of selectivity of both the LDAEP and BDNF for the serotonergic system, the findings of the Lang et al (2005) study need to be interpreted with caution.…”
mentioning
confidence: 99%
“…Sir Lang et al (2005) reported a negative association between serum brain-derived neurotrophic factor (BDNF) levels and central serotonergic neurotransmission as measured by the loudness dependence (LD) of the auditory-evoked potential (AEP). The authors suggest that low serum BDNF concentrations reflect low central serotonergic neurotransmission as indicated by the strong LD of the AEP.…”
mentioning
confidence: 99%